Digital Capability as a Mediating Mechanism Between Human Capital, Market Competition, and Operational Sustainability: Evidence from Premium Aesthetic Services in Indonesia - Pertiwi, A.A. Putu Sandra; Gunardi, Wani Devita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The research focuses on Pinky Treatment, a non-invasive aesthetic service positioned as a premium offering targeting upper–middle market segments with relatively low market awareness, thereby requiring continuous education and promotion through digital capabilities. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) on data collected from 120 respondents through structured questionnaires. Four latent variables, human capital, market competition, digital capability, and operational sustainability, were analyzed using SmartPLS 4. The results indicate that Human Capital (β = 0.475; p < 0.001) and Market Competition (β = 0.254; p = 0.001) have positive and significant effects on Digital Capability. Furthermore, Digital Capability has a positive and significant effect on Operational Sustainability (β = 0.481; p < 0.001). However, Human Capital (β = 0.134; p = 0.131) and Market Competition (β = 0.100; p = 0.164) do not have significant direct effects on Operational Sustainability. These findings demonstrate that Digital Capability fully mediates the effects of human capital and market competition on operational sustainability. The research model exhibits a moderate explanatory power (R² = 0.356) and adequate predictive relevance (Q² > 0). The study concludes that digital capability is a critical factor in translating human resources and competitive market pressures into operational sustainability, particularly for premium services that require continuous market education and consistent promotional efforts. Although Pinky Treatment presents an attractive business opportunity due to its non-invasive nature, ease of licensing, high profit margins, and potential for cost efficiency, its operational sustainability is highly dependent on the ability of business actors to develop and manage digital capabilities. This study is limited to a single type of aesthetic service and a specific sample size; therefore, the generalizability of the findings should be approached with caution.